PERENCANAAN STRATEGI BERKELANJUTAN PROGRAM BANK SAMPAH MENGGUNAKAN INTEGRASI BALANCED SCORECARD DAN HOSHIN KANRI - Albert, Jonathan; Kosasih, Wilson; Kristina, Helena Juliana (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
Based on data from SIPSN, the total national waste generation consisting of 200 regencies or cities has reached 21.45 million tons in 2021. Of the total national waste pile, 7.13 million tons (33.26%) are still unmanaged. To help resolve this issue, PT NS together with PT M organized waste bank program which aims to build and develop more waste banks, but fact on the field showed that not all waste bank movements can run smoothly. Therefore, an analysis of the performance of waste bank services was carried out using the balanced scorecard and long-term strategic planning was conducted using hoshin kanri. From the results of the 9 prioritized strategic goals weighting, it was found that increase in profit has the greatest weight with value of 0.171. While new customer acquisition has the smallest weight with value of 0.070. From the performance evaluation carried out with objective matrix and traffic light system, there are 4 performance indicators in green, 1 in yellow, and 4 in red. After this, strategic planning can be carried out using the hoshin kanri strategy map to provide long-term strategy that can help waste banks in the program to operate sustainably.